Correlation between alterations in blood flow of malignant lymphomas after induction chemotherapies and clinical outcomes: a pilot study utilising contrast-enhanced ultrasonography for early interim evaluation of lymphoma treatment. Issue 7 (July 2021) - Kumagawa, M.; Matsumoto, N.; Miura, K.; Ogawa, M.; Takahashi, H.; Hatta, Y.; Kondo, R.; Koizumi, N.; Takei, M.; Moriyama, M.
Abstract : Aim: To clarify the utility of contrast-enhanced ultrasonography (CEUS) for interim evaluation of response to chemotherapy in lymphoma treatment. Materials and methods: CEUS was performed both before (day 0) and after the treatment (7 and/or 14 days), and a time–intensity curve was obtained. The patients were divided into two groups (complete remission [CR] group and non-CR group) according to the results of conventional response evaluation, and peak enhancement (PE), time to peak enhancement, perfusion index (PI), the total area under the curve during wash-in (AUC-in), and the total AUC were compared between the groups. Results: Among 27 patients with various types of lymphoma, the median change ratio of PE and PI at day 7 evaluation were significantly different between the CR group and the non-CR group (0.81 versus 1.39, p= 0.017 for PE and 0.92 versus 2.09, p= 0.010 for PI). The change ratio of PE < 1.09 (specificity: 86%; sensitivity, 88%) and PI < 1.65 (specificity: 86%; sensitivity: 94%) distinguished CR from non-CR. Patients who achieved a PE change ratio <1.09 or a PI change ratio <1.65 had significantly better estimated progression-free survival ( p< 0.001). Conclusion: The present study demonstrated that changes in tumour perfusion parameters evaluated with CEUS at 1 week after the treatment initiation were significantly different between lymphoma patients in CR group and non-CR group. Alterations in perfusion parameters evaluated via CEUS could impact the prognosis of lymphoma patients. Highlights: Contrast-enhanced ultrasonography can evaluate treatment response in malignancies. The significance of interim imaging analysis during the treatment of lymphomas. Contrast-enhanced ultrasonography is useful to predict the prognosis of lymphoma.